Efektivitas Penggunaan Instagram Dalam Membentuk Citra (Studi Pada Palembang Beatbox Family) - Nurul Izzah; Sumaina Duku; Ahmad Harun Yahya (CV. ITTC INDONESIA, 2023)
The rapid development of information and communication technology supports the need for public information servis through the media. Various types of media appear as intermediaries that can make it easier for humans to convey their communication activities through the use of the internet, one of which is through Instagram. The rise of Instgram which is more used as a medium to interect with others makes it a new phenomenon as a medium of communication. The research focus in this study is How is the effectiveness of using Instagram social media in shaping the image of the Palembang Beatbox Family. This study aims to find out how effective the use of social media Instagram in shaping the image of Palembang Beatbox Family. The research method used is qualitative while the type of research is descriptive and while the data collection methods used are observation, interview, and documentation methods. From the results of reseacrches’ research, it can be concluded that the Palembang Beatbox Family community uses sosial media instagram as a means of introducing what the beatbox community in Palembang is to the general public and the use of instagram as a promotional medium is quite effective in increasing it’s image and popularity on Instagram account @palembangbeatboxfam itself seen from various kinds of pots activities and event carried out. This can be seen from the many interesting uploads presented, with the use of social media Instagram as a means of promotion.